The Effect of Five-Day Dry Immersion on the Nervous and Metabolic Mechanisms of the Circulatory System - Rusanov, Vasily B.; Pastushkova, Ludmila Kh.; Larina, Irina M.; Chernikova, Anna G.; Goncharova, Anna G.; Nosovsky, Andrei M.; Kashirina, Daria N.; Brzhozovsky, Alexander G.; Navasiolava, Nastassia; Kononikhin, Alexey S.; Kussmaul, Anna R.; Custaud, Marc-Antoine; et al. (Frontiers in Physiology, 2020)
The purpose of the study was to investigate the regulatory and metabolic changes in the circulatory system when simulating microgravity conditions in a five-day dry immersion. These changes reflect the adaptation processes characteristic for the initial stages of a space flight or a short-duration space flight. Studies were conducted with 13 healthy male volunteers aged 21 to 29 years. The assessment of regulatory and metabolic processes in the circulatory system was based on the heart rate variability (HRV) and urine proteomic profile analysis. It was found that the restructuring of hemodynamics during 5 days hypogravity begins with the inclusion of the nervous circuit of regulation, and for manifestations at the body fluids protein composition level and activation of the metabolic regulation, these periods are apparently insufficient. Perhaps this is due to the fact that the metabolic regulation, being evolutionarily ancient and genetically determined, is more stable and requires more time for its pronounced activation when stimulated by extreme life conditions.